Additive manufacturing applications for metals and composites - Balasubramanian, K. R., 1976-; Senthilkumar, V. (Advances in civil and industrial engineering (ACIE) book series., 2020)
"This book provides research on advancing methods and technological developments within additive manufacturing practices. Special attention is paid to the material design of additive manufacturing of parts, the choice of feedstock materials, the metallurgical behavior and synthesis principle during the manufacturing process, and the resulted microstructures and properties, as well as the relationship between these factors"--